Predisposition to Tartar following Fixed Retainers in a Population with a Healthy Periodontium: A Prospective Study - El hazzat, Wissam; Bilal , Amine; Zaoui, Fatima; Bahije, Loubna (Integrative Journal of Medical Sciences, 2022)
Introduction: Fixed retainers are systematically used after the orthodontic treatment to avoid recurrence. The continued presence of retainers creates difficult areas to clean, which can lead to plaque build-up and the formation of tartar, which can lead to gum inflammation and even periodontal disease. The objective of our study is to follow the evolution of periodontal indices after wearing the fixed retainer in patients with healthy periodontium treated in a dental office in Rabat. Materials and Methods: This was a prospective descriptive-analytical study that targeted 38 patients with a wire-type retainer device bonded in the city of Rabat. During our survey, we used a questionnaire divided into two parts. The first part was reserved for the patient, who answered questions about oral hygiene habits and information about the retainer. The second part concerned the methods and materials used by the orthodontist. Moreover, a clinical card included periodontal data collected on anterior teeth with a fixed retainer and was filled out during a physical examination. Results: An accumulation of dental plaque is observed mainly in the mandible in a moderate way visible to the naked eye in 69% of patients; this accumulation of plaque increases with the age of the retainer, especially in the mandible. Gingival inflammation manifested by spontaneous or induced bleeding is seen moderately in the mandible in 62% of patients. Mild-to-moderate bleeding in the maxilla in 54% of patients, a deposit of supragingival tartar covering a maximum of one-third of the tooth surface, mainly at the mandibular incisors in 66% of patients, and no bone loss related to fixed retainers in the anterior area of the mandible and maxilla have been reported despite the age of the retainer. The comparison of periodontal indices over three different wearing times showed statistically significant deterioration of periodontal health over time, especially at the mandibular incisors. Conclusion: Given the significant impact on periodontal health, this study made us aware of the importance of regularly monitoring oral hygiene during the contention phase.